Integrating Islamic Values into Indonesian Language Instruction: Developing Polite Communication among Elementary School Students - Zahro, Siti Fatimatuz; Rahayu S, Putri; Miftachudin, Miftachudin (AT-TURATS, 2025)
The phenomenon of declining communication politeness among elementary school students shows the importance of value-based learning strategies. This article discusses how Indonesian language learning can enhance Islamic values and foster polite communication skills among learners. This research uses qualitative techniques with a case study design at SD Negeri Cipondoh Makmur, which combines observation, interviews, and documentation on learners, teachers, and parents. Language skills (listening, reading and viewing, speaking and presenting, and writing) are combined with the values of qaulan sadida (truthful speech), qaulan ma'rufa (good speech), and qaulan layyina (gentle speech). The research findings show that this learning technique not only improves language skills but also develops communication ethics and learners' character in an Islamic social environment. The role of the teacher as a model of civilized communication proved important in increasing learners' awareness and habituation to polite behavior in the classroom and at home. Thus, the integration of Islamic values into Indonesian language learning strengthens character building in line with religious teachings.Fenomena menurunnya kesantunan berkomunikasi peserta didik sekolah dasar menunjukkan pentingnya strategi pembelajaran berbasis nilai. Artikel ini membahas tentang bagaimana pembelajaran bahasa Indonesia dapat meningkatkan nilai-nilai Islam dan menumbuhkan keterampilan berkomunikasi santun di kalangan peserta didik. Penelitian ini menggunakan teknik kualitatif dengan desain studi kasus di SD Negeri Cipondoh Makmur, yang menggabungkan observasi, wawancara, dan dokumentasi pada peserta didik, guru, dan orang tua. Keterampilan berbahasa (menyimak, membaca dan memirsa, berbicara dan mempresentasikan, dan menulis) dipadukan dengan nilai-nilai qaulan sadida (ucapan yang benar), qaulan ma'rufa (ucapan yang baik), dan qaulan layyina (ucapan yang lembut). Temuan penelitian menunjukkan bahwa teknik pembelajaran ini tidak hanya meningkatkan keterampilan berbahasa tetapi juga mengembangkan etika komunikasi dan karakter peserta didik dalam lingkungan sosial Islam. Peran guru sebagai model komunikasi yang beradab terbukti penting dalam meningkatkan kesadaran dan pembiasaan peserta didik terhadap perilaku santun di kelas dan di rumah. Dengan demikian, integrasi nilai-nilai Islam ke dalam pembelajaran bahasa Indonesia memperkuat pembentukan karakter yang selaras dengan ajaran agama.